• 7a+3*(a-b)
    -5a+2*(2,5a-b)
    2x-3*(x-y)
    -4x+2*(2x-5)

    Упростите пж

Ответы 2

  • Ответ:

    -10 - 3*b - 3*x + 3*y + 5*a + 2*x*(-2*b + 5*a)

    Пошаговое объяснение:

    • Автор:

      oakley13
    • 5 лет назад
    • 0
  • 7a + 3(a - b) = 7a + 3a - 3b = 10a - 3b

     - 5a + 2(2.5a - b) =  - 5a + 5a - 2b =  - 2b

    2x - 3(x - y) = 2x - 3x + 3y =  - 1x + 3y

     - 4x + 2(2x - 5) =  - 4x + 4x - 10 =  - 10

  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years